A fly ash-based sintered ceramsite proppant and its preparation method and use
By acid treatment, low-aluminum fly ash is activated and combined with the characteristics of high-aluminum fly ash, the particle yield and spherical degree of fly ash-based sintered ceramic proppant is improved, and the problems of low fly ash utilization rate and poor proppant performance in the existing technology are solved, and efficient and economical fly ash resource utilization is achieved.
Patent Information
- Application Number
- CN202210503285.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-09
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-05-09
AI Technical Summary
In the prior art, fly ash utilization rate is low, proppant particle output rate is low, and the spherical degree is poor, so further improvement is needed.
Low-aluminum fly ash is activated by acid treatment, silica gel is produced as binder, and mullite and corundum in high-aluminum fly ash are used as skeleton support to improve the strength and sphericality of the proppant.
The high particle yield and high spherical degree of fly ash-based sintered ceramic proppant is achieved, which reduces the sintering temperature, saves energy consumption, and improves the utilization rate of fly ash and the strength of the product.
Smart Images

Figure CN117070207B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource utilization of industrial solid waste, and in particular to a fly ash-based sintered ceramsite proppant and a preparation method and application thereof. Background Art
[0002] Fly ash is the fly ash produced by the combustion of boilers in coal-fired power plants, with an annual production of nearly 600 million tons. At present, the comprehensive utilization rate is only about 70%, and the fly ash that cannot be used is mainly stored. If it is not properly handled, it will cause serious pollution to the atmosphere, soil and water environment, and even endanger human health.
[0003] Fly ash has a complex composition. In terms of mineral composition, it mainly includes crystalline phase (such as quartz, mullite, corundum, etc.), glass phase and unburned carbon, etc. In terms of chemical composition, fly ash is mainly composed of metal oxides, with aluminum oxide and silicon oxide accounting for nearly 80%. As the proportion of coal-fired power generation in the power supply structure will remain at a high level, how to solve the contradiction between the growing production and accumulation of fly ash and the environment and economy has become an urgent problem to be solved.
[0004] At present, there have been many studies on using fly ash as raw material to prepare proppants required in oil production.
[0005] CN102899015A discloses a low-density ceramsite proppant prepared by using fly ash and a preparation method thereof. The proppant comprises the following raw material components by weight percentage: 60-80% of bauxite, 10-30% of fly ash and 5-10% of manganese powder. Compared with coal gangue, the low-density ceramsite proppant prepared by using fly ash as raw material can significantly reduce the breakage rate of the low-density ceramsite proppant, reduce the volume density and turbidity of the ceramsite proppant, improve the product quality of the ceramsite proppant, reduce the cost, and solve the environmental pollution caused by the discharge of fly ash.
[0006] CN107365579A discloses a petroleum fracturing proppant produced by processing fly ash as raw material and a preparation method thereof, wherein the raw materials include fly ash, waste ceramics, basalt and manganese ore powder, wherein fly ash and waste ceramics account for 70-90% of the total weight of the raw materials, the weight ratio of fly ash to waste ceramics is (2-2.5):1, basalt and manganese ore powder account for 10-30% of the total weight of the raw materials, the weight ratio of basalt to manganese ore powder is (4-5):1, and the product is processed and produced through the process steps of crushing, mixing, grinding, impurity removal, thermal processing, etc. The preparation method has simple process steps and is easy to implement. The produced product has the characteristics of low apparent density and strong crushing resistance. The raw materials used are all recycled materials or widely available materials, which is energy-saving and environmentally friendly, with low production cost and low resource consumption.
[0007] CN102718523A discloses a method for preparing a fracturing proppant using fly ash, wherein fly ash, alumina powder, barium carbonate and alumina chopped fibers are mixed, and then a gum aqueous solution is added for mixing and wet grinding to form a mixed slurry, and a pressure spray granulator is used for granulation, and the particles are placed in an alumina crucible and placed in a silicon carbon rod resistance furnace, and the temperature is increased from room temperature to 1230°C at a heating rate of 5-10°C / min, and the temperature is kept for 0.5-1h, and the temperature is increased to 1350-1400°C at a heating rate of 5-7°C / min, and the temperature is kept for 2-3h, and the mixture is taken out after natural cooling in the furnace, and a 20-40 mesh sieve is passed to obtain a composite fracturing proppant. The method introduces alumina chopped fibers, integrates the concept of composite materials into non-dense ceramsite proppant, and provides the fibers (whiskers) necessary for strengthening and toughening by means of high-temperature reaction self-generation, and prepares a composite fracturing proppant with high strength, high toughness, low density and low breakage rate by means of fiber reinforcement and particle reinforcement.
[0008] However, the above method has a low utilization rate of fly ash, and the particle yield of the proppant is low and the sphericity is poor, which needs further improvement.
[0009] Therefore, it is of great significance to develop a fly ash-based sintered ceramsite proppant with high granulation rate and high sphericity of the proppant during granulation, as well as a preparation method and use thereof. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a fly ash-based sintered ceramsite proppant and its preparation method and use. According to the different characteristics of low-aluminum fly ash and high-aluminum fly ash in chemical composition and physical phase, the low-aluminum fly ash is first activated by acid treatment to produce silica gel, which acts as a binder in the granulation process of the proppant. At the same time, the low melting point substances in the low-aluminum fly ash are used to reduce the sintering temperature, saving energy consumption in the production process of ceramsite proppant; at the same time, the high-aluminum fly ash is rich in high-strength mullite and corundum phases. Mullite and corundum play a skeleton support role in the proppant, improving the strength of the proppant particles. The present invention reduces the production cost of ceramsite proppant while realizing the high-value utilization of fly ash solid waste, which has both economic and environmental significance.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a method for preparing a fly ash-based sintered ceramsite proppant, the preparation method comprising the following steps:
[0013] (1) mixing the first fly ash with an acid solution and performing an acid activation treatment to obtain acid-activated fly ash;
[0014] (2) mixing 10 to 40 parts by weight of the acid-activated fly ash with 50 to 100 parts by weight of the second fly ash to obtain a mixed powder;
[0015] (3) After mixing water with the mixed powder, granulation, drying and sintering are performed in sequence to obtain the fly ash-based sintered ceramsite proppant.
[0016] The preparation method of the fly ash-based sintered ceramsite proppant of the present invention firstly treats the first fly ash, i.e., low-aluminum fly ash, by acid activation, so that the low-aluminum fly ash undergoes a chemical reaction, wherein the amorphous alumina and a small amount of low-melting-point substances are dissolved by an acid solution, and the amorphous silica forms a large amount of active silica gel after acid activation. A large amount of silanol groups exist on the surface of the silica gel. During the granulation process, the hydroxyl groups between the silica gel particles and on the surface of the silica gel and the fly ash are easy to form hydrogen bonds, which is beneficial to improving the ball formation rate and the ball strength. At the same time, the calcium oxide in the low-aluminum fly ash can increase the liquid phase amount and mass transfer rate in the system during the high-temperature sintering process, play a good role as a flux, so that the activated fly ash has good sintering performance, and the sintering temperature of the proppant is significantly reduced. Afterwards, the acid-activated fly ash is mixed with the second fly ash, i.e., high-aluminum fly ash. The addition of high-aluminum fly ash, on the one hand, utilizes the mullite in the high-aluminum fly ash as the main crystal phase of the proppant to improve the strength of the proppant particles; on the other hand, it can greatly increase the fly ash dosage in the present invention, and the proportion of fly ash in the mixed powder is ≥80%, thereby realizing the high-value utilization of fly ash.
[0017] In the present invention, 10 to 40 parts of the acid-activated fly ash are mixed with 50 to 100 parts of the second fly ash by weight to obtain a mixed powder; within the appropriate ratio range, the firing temperature can be fully reduced, the energy consumption can be reduced, and the granulation and balling effect is good. The liquid phase fills the voids in the mullite structure, so that the proppant has a low density and high strength. The preparation method of the fly ash-based sintered ceramsite proppant of the present invention reduces the firing temperature by 100 to 200°C compared with the typical petroleum fracturing proppant, belongs to a low-temperature firing process, can greatly save the energy consumption in the production process of the ceramsite proppant, reduce the production cost, and has a significant economic advantage.
[0018] The preparation method of the present invention uses only water as a physical binder in the granulation process. Compared with most proppants on the market that use organic binders, the present invention does not generate waste gas pollution during the sintering process. In addition, after the water evaporates, pores are left inside the proppant, which reduces the density of the proppant, facilitates transportation, reduces the requirements for fracturing fluid and the damage to equipment during backflow.
[0019] The 10-40 parts of the acid-activated fly ash in the present invention can be, for example, 10 parts, 11 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 38 parts or 40 parts, etc.; the 50-100 parts of the second fly ash in the present invention can be, for example, 50 parts, 55 parts, 60 parts, 80 parts, 90 parts, 95 parts, 99 parts or 100 parts, etc.
[0020] Preferably, the first fly ash in step (1) is low-aluminum fly ash.
[0021] Preferably, the content of aluminum oxide in the first fly ash is ≤35%, for example, it may be 35%, 32%, 30%, 28%, 25%, 23%, 20%, 15%, 10% or 5%, etc.
[0022] Preferably, the calcium oxide content in the first fly ash is >10wt%, for example, it can be 10.5wt%, 12wt%, 15wt%, 17wt%, 19wt%, 21wt%, 23wt% or 25wt%, etc., preferably >15wt%.
[0023] Preferably, the content of silicon dioxide in the first fly ash is >30wt%, for example, it can be 30.5wt%, 32wt%, 35wt%, 38wt%, 40wt%, 42wt%, 45wt%, 48wt%, 50wt%, 55wt% or 60wt%, etc.
[0024] Preferably, the first fly ash is subjected to a first screening treatment before being mixed with the acid solution.
[0025] Preferably, the size of the sieve holes in the first screening process is 100-300 meshes, for example, 100 meshes, 150 meshes, 200 meshes, 250 meshes or 300 meshes.
[0026] Preferably, the acid solution in step (1) comprises H 2 SO 4 solution and / or HCl solution.
[0027] Preferably, the concentration of the acid solution is 0.5-3 mol / L, for example, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L.
[0028] The present invention preferably has a concentration of the acid solution of 0.5 to 3 mol / L. When the concentration of the acid solution is too low, the activation degree of amorphous silica in the low-aluminum fly ash is low, and a good bonding effect cannot be achieved during the granulation process, resulting in a decrease in the sphericity of the fly ash-based sintered ceramsite proppant; when the concentration of the acid solution is too high, too much low-melting-point oxides such as calcium oxide and magnesium oxide will react, resulting in a small amount of liquid phase generated by the mixed powder during the sintering process, which cannot promote low-temperature sintering, thereby affecting the overall performance of the fly ash-based sintered ceramsite proppant.
[0029] Preferably, the ratio of the volume of the acid solution to the mass of the first fly ash is 5 to 15 L / g, for example, it can be 5 L / g, 6 L / g, 7 L / g, 8 L / g, 9 L / g, 10 L / g, 12 L / g or 15 L / g, etc., preferably 5 to 10 L / g.
[0030] The present invention preferably has a volume ratio of the acid solution to the mass ratio of the first fly ash of 5 to 15 L / g, so that the low-aluminum fly ash can react well, the amorphous alumina and a small amount of low-melting-point substances therein are dissolved by the acid solution, and the amorphous silicon dioxide forms silica gel after acid activation, which is conducive to ball formation during the granulation process. When the ratio of the two is too large or too small, the performance of the fly ash-based sintered ceramsite proppant obtained in the end will deteriorate.
[0031] Preferably, the temperature of the acid activation treatment is 50-130°C, for example, 50°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or 130°C.
[0032] Preferably, the acid activation treatment time is 0.5 to 12 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 8 h, 10 h or 12 h.
[0033] The present invention preferably uses an acid activation treatment at a temperature of 50 to 130°C and a time of 0.5 to 12 hours. When the temperature of the acid activation treatment is too low and the treatment time is too short, the activation degree of the low-aluminum fly ash will be insufficient to achieve the activity of the activation reaction; when the temperature of the acid activation treatment is too high and the treatment time is too long, overburning will occur, the structure of the low-aluminum fly ash will be destroyed, and the overall performance of the final fly ash-based sintered ceramsite proppant will be affected.
[0034] Preferably, the acid-activated fly ash is dried after the acid activation treatment.
[0035] Preferably, the second fly ash in step (2) is high-aluminum fly ash.
[0036] Preferably, the content of alumina in the second fly ash is >35wt%, for example, it may be 35.5wt%, 38wt%, 40wt%, 42wt%, 45wt%, 48wt%, 50wt%, 55wt% or 60wt%, etc., preferably ≥40wt%.
[0037] Preferably, the silicon dioxide content in the second fly ash is >30wt%, for example, it can be 30.5wt%, 32wt%, 35wt%, 36wt%, 38wt%, 40wt%, 42wt%, 45wt%, 48wt%, 50wt%, 55wt% or 60wt%, etc.
[0038] Preferably, the second fly ash is subjected to a second screening treatment before being mixed with the acid-activated fly ash.
[0039] Preferably, the size of the sieve holes in the second screening process is 60-300 mesh, for example, 60 mesh, 80 mesh, 100 mesh, 150 mesh, 200 mesh, 250 mesh or 300 mesh, etc., preferably 100-150 mesh.
[0040] Preferably, the mixed powder in step (2) further comprises 0.1 to 10 parts by mass of bauxite, for example, 0.1 parts, 1 parts, 3 parts, 5 parts, 8 parts, 9 parts or 10 parts.
[0041] In the present invention, the mixed powder preferably also includes 0.1 to 10 parts by mass of bauxite. The addition of bauxite can adjust the aluminum-silicon ratio of the system, densify the proppant, and improve the strength of the finally obtained fly ash-based sintered ceramsite proppant.
[0042] Preferably, the content of aluminum oxide in the bauxite is >60wt%, for example, it can be 60.5wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt% or 95wt%, etc.
[0043] Preferably, the bauxite is subjected to a third screening treatment before being mixed with the acid-activated fly ash.
[0044] Preferably, the size of the sieve holes in the third screening process is 100-300 meshes, for example, it can be 100 meshes, 150 meshes, 200 meshes, 250 meshes or 300 meshes, etc., preferably 100-200 meshes.
[0045] Preferably, the mixed powder further comprises 0.1 to 10 parts by weight of kaolin, for example, 0.1 parts, 1 parts, 3 parts, 5 parts, 8 parts, 9 parts or 10 parts by weight.
[0046] In the present invention, the mixed powder preferably further comprises 0.1 to 10 parts by weight of kaolin. The addition of kaolin can also increase the aluminum-silicon ratio, and improve the density and strength of the finally obtained fly ash-based sintered ceramsite proppant.
[0047] Preferably, the kaolin is subjected to a fourth screening treatment before being mixed with the acid-activated fly ash.
[0048] Preferably, the size of the sieve holes in the fourth screening process is 100-300 meshes, for example, it can be 100 meshes, 150 meshes, 200 meshes, 250 meshes or 300 meshes, etc., preferably 100-200 meshes.
[0049] Preferably, the mass fraction of water in step (3) in the mixed powder is 10-25wt%, for example, it can be 10wt%, 12wt%, 14wt%, 15wt%, 18wt%, 20wt%, 22wt% or 25wt%.
[0050] The present invention preferably has a mass fraction of water in the mixed powder of 10 to 25 wt%. By strictly controlling the amount of water added during the granulation process, the sphericity and particle size of the finally obtained fly ash-based sintered ceramsite proppant can be ensured. By controlling the water content in the reaction mixture after adding water during the granulation process, the optimal technical effect can be achieved.
[0051] Preferably, the mixing time of the water and the mixed powder is 1 to 30 min, for example, it can be 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, etc.
[0052] Preferably, the mixing of water and mixed powder includes step-by-step mixing or one-time mixing, preferably step-by-step mixing.
[0053] Preferably, the stepwise mixing includes first adding 5-15wt% of water to the mixed powder and mixing with the whole mixed powder for 0.5-20min, and then adding the remaining water to continue mixing. The water accounting for 5-15wt% of the mixed powder can be, for example, 5wt%, 8wt%, 9wt%, 10wt%, 12wt%, 14wt% or 15wt%, etc.; the mixing time of 0.5-20min can be, for example, 0.5min, 1min, 1.2min, 1.5min, 1.8min, 2min, 2.5min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 12min, 14min, 16min, 18min or 20min, etc.
[0054] The mixing of water and mixed powder in the present invention can be carried out in a granulation treatment device, that is, the water and mixed powder are first mixed in the granulation treatment device, and then the granulation treatment is carried out.
[0055] Preferably, the equipment used in the granulation process includes any one of an inclined intensive mixer, a sugar coating pan or a disc granulator, preferably an inclined intensive mixer.
[0056] Preferably, the barrel rotation speed of the inclined intensive mixer is 20 to 80 r / min, for example, it can be 20 r / min, 30 r / min, 40 r / min, 50 r / min, 60 r / min, 70 r / min or 80 r / min.
[0057] Preferably, the rotor speed of the inclined intensive mixer is 500-4000 r / min, for example, it can be 500 r / min, 1000 r / min, 1500 r / min, 2000 r / min, 2500 r / min, 3000 r / min, 3500 r / min or 4000 r / min.
[0058] Preferably, the granulation treatment time is 1 to 30 min, for example, it can be 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 15 min, 20 min, 25 min or 30 min.
[0059] Preferably, the sintering process in step (3) includes heating the semi-finished product obtained by granulation from room temperature to a sintering temperature and then keeping the temperature.
[0060] Preferably, the heating rate is 5 to 20°C / min, for example, it may be 5°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 12°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min, etc.
[0061] Preferably, the sintering temperature is 1200-1700°C, for example, it may be 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C or 1700°C.
[0062] The preferred sintering temperature of the present invention is 1200-1700° C., which can produce a proppant with excellent performance suitable for use in the oil or natural gas extraction process. When the sintering temperature is too high or too low, the performance of the fly ash-based sintered ceramsite proppant obtained in the end will be affected.
[0063] Preferably, the insulation time is 0.5 to 10 h, for example, 0.5 h, 2 h, 4 h, 5 h, 6 h, 8 h or 10 h.
[0064] Preferably, the heat preservation is followed by natural cooling with the furnace.
[0065] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0066] (1) mixing the first fly ash with an acid solution having a concentration of 0.5 to 3 mol / L, performing an acid activation treatment, and obtaining acid-activated fly ash;
[0067] The first fly ash is low-aluminum fly ash; the content of aluminum oxide in the first fly ash is ≤35%, the content of calcium oxide is >10wt%, and the content of silicon dioxide is >30wt%; the first fly ash is subjected to a first screening process before being mixed with the acid solution; the size of the sieve hole in the first screening process is 100-300 mesh; the acid solution includes H 2 SO 4 solution and / or HCl solution; the ratio of the volume of the acid solution to the mass of the first fly ash is 5 to 15 L / g; the temperature of the acid activation treatment is 50 to 130° C.; the time of the acid activation treatment is 0.5 to 12 hours; after the acid activation treatment, the acid-activated fly ash is dried;
[0068] (2) mixing 10 to 40 parts by weight of the acid-activated fly ash with 50 to 100 parts by weight of the second fly ash to obtain a mixed powder;
[0069] The second fly ash is high-aluminum fly ash; the content of aluminum oxide in the second fly ash is greater than 35wt%, and the content of silicon dioxide is greater than 30wt%. The second fly ash is subjected to a second screening process before being mixed with the acid-activated fly ash; the size of the sieve holes in the second screening process is 60-300 meshes; the mixed powder further includes 0.1-10 parts by weight of bauxite; the content of aluminum oxide in the bauxite is greater than 60wt%; the bauxite is subjected to a third screening process before being mixed with the acid-activated fly ash; the size of the sieve holes in the third screening process is 100-300 meshes; the mixed powder further includes 0.1-10 parts by weight of kaolin; the kaolin is subjected to a fourth screening process before being mixed with the acid-activated fly ash; the size of the sieve holes in the fourth screening process is 100-300 meshes;
[0070] (3) After mixing water with the mixed powder for 1 to 30 minutes, granulation treatment, drying and sintering treatment are sequentially performed for 1 to 30 minutes to obtain the fly ash-based sintered ceramsite proppant; the mass fraction of water in the mixed powder is 10 to 25 wt%; the mixing of water and the mixed powder includes step-by-step mixing or one-time mixing; the step-by-step mixing includes first adding water with a mass fraction of 5 to 15 wt% of the mixed powder and mixing with the whole mixed powder for 0.5 to 20 minutes, and then adding the remaining water to continue mixing ; The equipment used in the granulation treatment includes any one of an inclined intensive mixer, a sugar coating pan or a disc granulator; the barrel speed of the inclined intensive mixer is 20 to 80 r / min; the rotor speed of the inclined intensive mixer is 500 to 4000 r / min; the sintering process includes heating the semi-finished product obtained by the granulation treatment from room temperature at a heating rate of 5 to 20°C / min to a sintering temperature of 1200 to 1700°C, then keeping the temperature for 0.5 to 10 hours and then cooling it naturally with the furnace.
[0071] In a second aspect, the present invention further provides a fly ash-based sintered ceramsite proppant, wherein the fly ash-based sintered ceramsite proppant is prepared by the preparation method of the fly ash-based sintered ceramsite proppant described in the first aspect.
[0072] In a third aspect, the present invention further provides a use of a fly ash-based sintered ceramsite proppant, wherein the fly ash-based sintered ceramsite proppant described in the second aspect is used in the process of oil or natural gas extraction.
[0073] The fly ash-based sintered ceramsite proppant of the present invention is used in the process of oil and natural gas exploitation, and can greatly improve the recovery rate of oil and gas wells.
[0074] Compared with the prior art, the present invention has at least the following beneficial effects:
[0075] (1) The method for preparing fly ash-based sintered ceramsite proppant provided by the present invention utilizes the characteristic that low-aluminum fly ash produces a large amount of active silica gel after acid activation to carry out proppant granulation treatment, so that the fly ash raw material is conducive to agglomeration into balls, which makes up for the problems of low fly ash granulation rate and poor sphericity, and greatly increases the proportion of fly ash to more than 80%. At the same time, due to the high content of amorphous silicon and calcium oxide in low-aluminum fly ash, a large amount of liquid phase is produced during the sintering process, which accelerates the mass transfer rate, reduces the sintering temperature, improves the product strength, saves energy and reduces consumption, and can realize the high-value utilization of fly ash solid waste;
[0076] (2) The preparation method of the fly ash-based sintered ceramsite proppant provided by the present invention uses water as a physical binder during the granulation process. Compared with most proppants on the market that use organic binders, the present invention does not generate waste gas pollution during the sintering process. In addition, after the water evaporates, pores are left inside the proppant, which reduces the density of the proppant, facilitates transportation, reduces the requirements for fracturing fluid and the damage to equipment during backflow;
[0077] (3) The method for preparing fly ash-based sintered expanded clay proppant provided by the present invention uses fly ash to replace primary resource bauxite to prepare expanded clay proppant, which can not only realize the high-value utilization of fly ash solid waste and alleviate the environmental problems caused by large-scale storage of fly ash, but also save bauxite resources and reduce the production cost of proppant, which has both economic and environmental significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Figure 1 The invention discloses a process flow chart of a method for preparing a fly ash-based sintered ceramsite proppant.
[0079] Figure 2 This is the XRD diagram of the fly ash-based sintered ceramsite proppant obtained in Example 1.
[0080] Figure 3 This is a SEM picture of the fly ash-based sintered ceramsite proppant obtained in Example 1 after being embedded, polished and etched with 20% HF acid at a magnification of 400 times.
[0081] Figure 4 This is a SEM picture of the fly ash-based sintered ceramsite proppant obtained in Example 1 after being embedded, polished and etched with 20% HF acid at a magnification of 12,000 times. DETAILED DESCRIPTION
[0082] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0083] The present invention provides a method for preparing a fly ash-based sintered ceramsite proppant, and the process flow chart of the preparation method is as follows: Figure 1 As shown, the preparation method comprises the following steps:
[0084] (1) mixing the first fly ash with an acid solution and performing an acid activation treatment to obtain acid-activated fly ash;
[0085] (2) mixing 10 to 40 parts by weight of the acid-activated fly ash with 50 to 100 parts by weight of the second fly ash to obtain a mixed powder;
[0086] (3) After mixing water with the mixed powder, granulation, drying and sintering are performed in sequence to obtain the fly ash-based sintered ceramsite proppant.
[0087] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0088] The low-aluminum fly ash in the following embodiments is fly ash produced by a thermal power plant in Hailar, Inner Mongolia Autonomous Region, wherein the content of aluminum oxide is 19wt%, the content of silicon dioxide is 39wt%, and the content of calcium oxide is 20wt%; the high-aluminum fly ash is fly ash produced by a thermal power plant in Daihai, Inner Mongolia Autonomous Region, wherein the content of aluminum oxide is 45wt%, and the content of silicon dioxide is 46wt%.
[0089] Example 1
[0090] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant, the preparation method comprising the following steps:
[0091] (1) Mix low-aluminum fly ash with 1.5 mol / L H 2 SO 4 The solution is fully stirred in a closed reactor for acid activation. After the reaction is completed, the slurry is filtered, washed and dried to obtain acid-activated fly ash;
[0092] The low aluminum fly ash and H 2 SO 4 The solution is subjected to a first screening process before mixing; the size of the sieve holes in the first screening process is 100 to 200 meshes; the H 2 SO 4 The volume ratio of the solution to the mass of the low-aluminum fly ash is 7 L / g; the temperature of the acid activation treatment is 85° C.; the time of the acid activation treatment is 1.5 h;
[0093] (2) Mixing 20 parts of the acid-activated fly ash and 80 parts of high-aluminum fly ash by weight to obtain a mixed powder;
[0094] The high-aluminum fly ash and the acid-activated fly ash are subjected to a second screening process before being mixed; the size of the sieve holes in the second screening process is 100-150 meshes; the mixed powder further includes 5 parts by weight of bauxite; the content of alumina in the bauxite is 75wt%; the bauxite and the acid-activated fly ash are subjected to a third screening process before being mixed; the size of the sieve holes in the third screening process is 100-200 meshes; the mixed powder further includes 5 parts by weight of kaolin; the kaolin and the acid-activated fly ash are subjected to a fourth screening process before being mixed; the size of the sieve holes in the fourth screening process is 100-200 meshes;
[0095] (3) mixing water with the mixed powder for 4 minutes, and then sequentially performing granulation, drying and sintering for 30 minutes to obtain the fly ash-based sintered ceramsite proppant;
[0096] The mass fraction of water in the mixed powder is 20wt%; the mixing of water and mixed powder is step-by-step mixing; the step-by-step mixing includes first adding water accounting for 15wt% of the mass fraction of the mixed powder and mixing with all the mixed powder for 1 minute, and then adding the remaining water to continue mixing; the equipment used in the granulation process is an inclined high-power mixer; the barrel speed of the inclined high-power mixer is 50r / min; the rotor speed of the inclined high-power mixer is 4000r / min; the sintering process includes heating the semi-finished product obtained by the granulation process from room temperature to a sintering temperature of 1310°C at a heating rate of 5°C / min, keeping the temperature for 2h, and then naturally cooling it with the furnace.
[0097] The XRD pattern of the fly ash-based sintered ceramsite proppant prepared in this example is as follows: Figure 2 shown.
[0098] from Figure 2 It can be seen that the main crystal phase of the fly ash-based sintered ceramsite proppant prepared in this embodiment is mullite, and the secondary crystal phase is calcium feldspar. The special long columnar cross structure of mullite improves the strength of the fly ash-based sintered ceramsite proppant, and the calcium oxide and amorphous silicon dioxide in the low-aluminum fly ash provide a liquid phase during the sintering process after acid activation, which promotes the reaction at a lower sintering temperature, and the precipitated calcium feldspar fills the mullite structure to play a supporting role.
[0099] The fly ash-based sintered ceramsite proppant prepared in this embodiment is shown in the SEM image at a magnification of 400 times after being embedded, polished and etched with 20% HF acid. Figure 3 As shown, the SEM image at 12000 times magnification is as follows Figure 4 shown.
[0100] from Figure 3 and Figure 4 It can be seen that the fly ash-based sintered ceramsite proppant sample has a high sphericity, mainly a staggered rod-shaped mullite structure, which can provide higher strength while reducing the volume density of the fly ash-based sintered ceramsite proppant.
[0101] Example 2
[0102] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant, the preparation method comprising the following steps:
[0103] (1) mixing low-aluminum fly ash and 1.5 mol / L HCl solution, fully stirring in a closed reactor, and performing acid activation treatment. After the reaction is completed, filtering, washing, and drying the slurry to obtain acid-activated fly ash;
[0104] The low-aluminum fly ash is subjected to a first screening treatment before being mixed with the HCl solution; the size of the sieve hole in the first screening treatment is 100 mesh; the ratio of the volume of the HCl solution to the mass of the low-aluminum fly ash is 7 L / g; the temperature of the acid activation treatment is 85° C.; and the time of the acid activation treatment is 1.5 h;
[0105] (2) Mixing 20 parts of the acid-activated fly ash and 40 parts of high-aluminum fly ash by weight to obtain a mixed powder;
[0106] The high-aluminum fly ash is subjected to a second screening process before being mixed with the acid-activated fly ash; the size of the sieve hole in the second screening process is 300 mesh; the mixed powder further includes 5 parts by weight of bauxite; the content of alumina in the bauxite is 80wt%; the bauxite is subjected to a third screening process before being mixed with the acid-activated fly ash; the size of the sieve hole in the third screening process is 100-200 mesh; the mixed powder further includes 5 parts by weight of kaolin; the kaolin is subjected to a fourth screening process before being mixed with the acid-activated fly ash; the size of the sieve hole in the fourth screening process is 100-200 mesh;
[0107] (3) mixing water and the mixed powder for 4 minutes, and then sequentially performing granulation, drying and sintering for 15 minutes to obtain the fly ash-based sintered ceramsite proppant;
[0108] The mass fraction of water in the mixed powder is 25wt%; the mixing of water and mixed powder is step-by-step mixing; the step-by-step mixing includes first adding water accounting for 15wt% of the mass fraction of the mixed powder and mixing with all the mixed powder for 3 minutes, and then adding the remaining water to continue mixing; the equipment used in the granulation process is an inclined high-power mixer; the barrel speed of the inclined high-power mixer is 50r / min; the rotor speed of the inclined high-power mixer is 3000r / min; the sintering process includes heating the semi-finished product obtained by granulation from room temperature to a sintering temperature of 1250°C at a heating rate of 5°C / min, keeping the temperature for 2h, and then naturally cooling it with the furnace.
[0109] Example 3
[0110] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant. The preparation method includes the following steps: 2 SO 4 Except that the concentration of the acid solution was changed to 0.5 mol / L, the rest was the same as in Example 1.
[0111] Example 4
[0112] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant. The preparation method includes the following steps: 2 SO 4 Except that the concentration of the acid solution was changed to 3 mol / L, the rest was the same as in Example 1.
[0113] Example 5
[0114] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant. The preparation method includes the following steps: 2 SO 4 Except that the ratio of the volume of the acid solution to the mass of the low-aluminum fly ash is changed to 5 L / g, the rest is the same as in Example 1.
[0115] Example 6
[0116] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant. The preparation method includes the following steps: 2 SO 4 Except that the ratio of the volume of the acid solution to the mass of the low-aluminum fly ash is changed to 15 L / g, the rest is the same as in Example 1.
[0117] Example 7
[0118] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant. The preparation method is the same as that of Embodiment 1 except that the sintering temperature in step (3) is replaced with 1200° C.
[0119] Example 8
[0120] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant. The preparation method is the same as that of Embodiment 1 except that the sintering temperature in step (3) is replaced with 1700° C.
[0121] Example 9
[0122] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant, which is the same as that of Embodiment 1 except that the insulation time in step (3) is replaced with 0.5 h.
[0123] Example 10
[0124] This embodiment provides a method for preparing a fly ash-based sintered ceramsite proppant. The preparation method is the same as that of Embodiment 1 except that the insulation time in step (3) is replaced with 10 hours.
[0125] Comparative Example 1
[0126] This comparative example provides a method for preparing a fly ash-based sintered ceramsite proppant, which is the same as Example 1 except that in step (2), 5 parts of the acid-activated fly ash are mixed with 120 parts of high-aluminum fly ash.
[0127] Comparative Example 2
[0128] This comparative example provides a method for preparing a fly ash-based sintered ceramsite proppant, which is the same as Example 1 except that in step (2), 80 parts of the acid-activated fly ash are mixed with 10 parts of high-aluminum fly ash.
[0129] Comparative Example 3
[0130] This comparative example provides a method for preparing a fly ash-based sintered ceramsite proppant, which is the same as Example 1 except that the high-aluminum fly ash in step (2) is replaced by low-aluminum fly ash from Xinjiang Autonomous Region, wherein the content of aluminum oxide in the low-aluminum fly ash is 23wt%, the content of silicon dioxide is 49wt%, and the content of calcium oxide is 6wt%.
[0131] Since high-aluminum fly ash is not used in this comparative example, mullite in the high-aluminum fly ash cannot be used as the main crystal phase of the proppant, resulting in the semi-finished product obtained by granulation treatment being in a molten state during the sintering process, and the final product, fly ash-based sintered ceramsite proppant, cannot be obtained.
[0132] Comparative Example 4
[0133] This comparative example provides a method for preparing a fly ash-based sintered ceramsite proppant, which is the same as Example 1 except that the low-aluminum fly ash in step (1) is replaced with Ordos high-aluminum fly ash, wherein the content of aluminum oxide in the high-aluminum fly ash is 37wt%, the content of silicon dioxide is 49wt%, and the content of calcium oxide is 3wt%.
[0134] Comparative Example 5
[0135] This comparative example provides a method for preparing a fly ash-based sintered ceramsite proppant, which is the same as Example 1 except that the acid activation treatment in step (1) is omitted and the low-aluminum fly ash is directly mixed with other raw materials.
[0136] According to the SY-T5108-2014 proppant performance test method for hydraulic fracturing and gravel packing operations, the crushing rate, bulk density and acid solubility of the fly ash-based sintered ceramsite proppant obtained in the above embodiments and comparative examples were tested at 35 MPa. The results are shown in Table 1.
[0137] Table 1
[0138]
[0139]
[0140] From Table 1 we can see that:
[0141] (1) It can be seen from Examples 1 to 10 that the fly ash-based sintered ceramsite proppant prepared by the method for preparing the fly ash-based sintered ceramsite proppant provided by the present invention has a crushing rate of less than 10.92% at 35 MPa, and under optimal conditions, the crushing rate can reach less than 6.29% at 35 MPa; the bulk density can reach less than 1.47%, and under optimal conditions, the bulk density can reach less than 1.28%; the acid solubility can reach less than 3.93%, and under optimal conditions, the acid solubility can reach less than 1.95%;
[0142] (2) Combining Example 1 with Examples 3 to 4, it can be seen that in step (1) of Example 1, H 2 SO 4 The concentration of the acid solution is 1.5 mol / L, which is lower than that of H in step (1) of Example 3 and Example 4. 2 SO 4 For the acid solution concentrations of 0.5 mol / L and 3 mol / L, respectively, the fly ash-based sintered ceramsite proppant in Example 1 has a crushing rate of 6.29% at 35 MPa, a bulk density of 1.32%, and an acid solubility of 2.37%, while the fly ash-based sintered ceramsite proppant in Example 3 has a crushing rate of 9.26% at 35 MPa, a bulk density of 1.47%, and an acid solubility of 3.46%, mainly because H 2 SO 4 The solution concentration is too low, resulting in low activation degree of low-aluminum fly ash, insufficient silica gel production, poor adhesion during granulation, and poor performance of the fly ash-based sintered ceramsite proppant obtained in the end; the fly ash-based sintered ceramsite proppant in Example 4 has a higher crushing rate than that in Example 1 at 35 MPa, and the overall performance is slightly worse, mainly because the H in Example 4 2 SO 4 The solution concentration is too high, so that the low melting point substances in the system are dissolved by acid, and the amount of liquid phase produced during the sintering process is small, which affects the performance of the fly ash-based sintered ceramsite proppant;
[0143] (3) Combining Example 1 with Examples 5 to 6, it can be seen that in step (1) of Example 1, H 2 SO 4 The ratio of the volume of the acid solution to the mass of the low-aluminum fly ash is 7 L / g, which is 2.3 L / g higher than that of the H in step (1) of Example 5 and Example 6. 2 SO 4The ratio of the volume of the acid solution to the mass of the low-aluminum fly ash is 5L / g and 15L / g respectively. The performance of the fly ash-based sintered ceramsite proppant in Example 1 is superior to that of Examples 5 and 6. The main reason is that the ratio of the volume of the acid solution to the mass of the first fly ash is within a specific range, which can make the low-aluminum fly ash react chemically well. The amorphous alumina and a small amount of low-melting-point substances are dissolved by the acid solution, and the amorphous silica forms silica gel after acid activation, which is conducive to ball formation during the granulation process. When the ratio of the two is too large or too small, the performance of the fly ash-based sintered ceramsite proppant obtained in the end will deteriorate;
[0144] (4) Combining Example 1 with Examples 7 to 8, it can be seen that the sintering temperature in step (3) of Example 1 is 1310°C. Compared with the sintering temperatures of 1200°C and 1700°C in step (3) of Example 7 and Example 8, respectively, the performance of the fly ash-based sintered ceramsite proppant in Example 7 is slightly worse than that in Example 1. The breakage rate of the fly ash-based sintered ceramsite proppant in Example 8 at 35 MPa is greatly increased to 10.92%, the bulk density is relatively large, which is 1.45%, and the acid solubility is relatively low, which is 2.04%. The overall performance is worse than that of Example 1. This shows that the present invention further preferably sets the sintering temperature in a specific range, which can improve the overall performance of the fly ash-based sintered ceramsite proppant finally obtained;
[0145] (5) Combining Example 1 with Examples 9 to 10, it can be seen that the insulation time in step (3) of Example 1 is 0.5 h. Compared with the insulation times in step (3) of Examples 9 and 10, which are 0.5 h and 10 h respectively, the breakage rate and acid solubility of the fly ash-based sintered ceramsite proppant in Examples 9 and 10 at 35 MPa are significantly higher than those in Example 1, and the performance is significantly deteriorated; thus, the present invention further preferably sets the insulation time within a specific range, which is beneficial to improving the overall performance of the fly ash-based sintered ceramsite proppant finally obtained;
[0146] (6) It can be seen from the combination of Example 1 and Comparative Examples 1-2 that, in step (2) of Example 1, 20 parts of the acid-activated fly ash are mixed with 80 parts of high-aluminum fly ash. Compared with the mixing of 10 parts of the acid-activated fly ash with 80 parts of high-aluminum fly ash in step (2) of Comparative Example 1 and the mixing of 80 parts of the acid-activated fly ash with 10 parts of high-aluminum fly ash in step (2) of Comparative Example 2, the crushing rates of the fly ash-based sintered ceramsite proppants in Comparative Examples 1 and 2 at 35 MPa are 20.51% and 3.03%, respectively. 2.84%, the performance deteriorated significantly; mainly because the amount of acid-activated fly ash added in Comparative Example 1 was too low, resulting in poor balling effect of the proppant during granulation and low granulation rate; less liquid phase was generated during the sintering process, which was not conducive to filling the gaps between fly ash particles, resulting in a non-dense system and increased breakage rate; in Comparative Example 2, due to the high amount of acid-activated fly ash added, the proppant was too sticky during the granulation process, and the particles were larger overall; during the sintering process, due to the presence of more low-melting-point substances, a large amount of liquid phase was generated, affecting the overall performance;
[0147] (6) It can be seen from Example 1 and Comparative Example 3 that in Comparative Example 3, since high-aluminum fly ash is not used, mullite in high-aluminum fly ash cannot be used as the main crystal phase of the proppant, and the content of low-melting-point substances in low-aluminum fly ash is high, resulting in too much low-melting-point substances in the system, causing the semi-finished product obtained by granulation treatment to be in a molten state during the sintering process, and the final product fly ash-based sintered ceramsite proppant cannot be obtained;
[0148] (7) It can be seen from Example 1 and Comparative Example 4 that low-aluminum fly ash was not used in Comparative Example 4, but high-aluminum fly ash was used for acid activation treatment. Since the content of amorphous silica in high-aluminum fly ash is relatively low, the content of silica gel produced after acid activation is relatively low, resulting in difficulty in forming balls during the granulation process; and the content of low-melting-point substances in high-aluminum fly ash is low, and the amount of liquid phase generated during the sintering process is too low, resulting in poor system density, thus resulting in poor performance of fly ash-based sintered ceramsite proppant;
[0149] (8) It can be seen from Example 1 and Comparative Example 5 that in Comparative Example 5, the low-aluminum fly ash was not subjected to acid activation treatment, and the silica gel formed by the amorphous silica in the low-aluminum fly ash after acid activation could not be utilized, resulting in difficulty in balling during the granulation process, and the amount of liquid phase generated during the sintering process was too low, and the system density was poor, thereby resulting in poor performance of the fly ash-based sintered ceramsite proppant.
[0150] In summary, the preparation method of fly ash-based sintered ceramsite proppant provided by the present invention obtains a fly ash-based sintered ceramsite proppant with excellent performance by mixing low-aluminum fly ash with high-aluminum fly ash after acid activation treatment. The method can achieve high-value utilization of fly ash and effectively alleviate the environmental pollution problem caused by fly ash accumulation, and can also reduce the raw material cost of ceramsite proppant and save a large amount of bauxite primary resources, which has good economic and environmental benefits.
[0151] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a fly ash-based sintered ceramsite proppant, characterized in that: The preparation method comprises the following steps: (1) mixing the first fly ash with an acid solution and performing an acid activation treatment to obtain acid-activated fly ash; Wherein, the first fly ash is low-aluminum fly ash; the content of aluminum oxide in the first fly ash is ≤35%; the content of calcium oxide in the first fly ash is >10wt%; the content of silicon dioxide in the first fly ash is >30wt%; The acid solution includes H2SO4 solution and / or HCl solution; the concentration of the acid solution is 0.5-3 mol / L; the ratio of the volume of the acid solution to the mass of the first fly ash is 5-15 L / g; (2) Mixing 10 to 40 parts by weight of the acid-activated fly ash and 50 to 100 parts by weight of the second fly ash to obtain a mixed powder; Wherein, the second fly ash is high-aluminum fly ash; the content of aluminum oxide in the second fly ash is greater than 35wt%; the content of silicon dioxide in the second fly ash is greater than 30wt%; (3) After mixing water with the mixed powder, granulation, drying and sintering are performed in sequence to obtain the fly ash-based sintered ceramsite proppant.
2. The preparation method according to claim 1, characterized in that: Step (1) The content of calcium oxide in the first fly ash is >15wt%.
3. The preparation method according to claim 1, characterized in that: The first fly ash is subjected to a first screening treatment before being mixed with the acid solution.
4. The preparation method according to claim 3, characterized in that: The size of the sieve holes in the first screening process is 100-300 meshes.
5. The preparation method according to claim 1, characterized in that: The ratio of the volume of the acid solution in step (1) to the mass of the first fly ash is 5-10 L / g.
6. The preparation method according to claim 1, characterized in that: The temperature of the acid activation treatment is 50-130°C.
7. The preparation method according to claim 1, characterized in that: The time of the acid activation treatment is 0.5 to 12 hours.
8. The preparation method according to claim 1, characterized in that: After the acid activation treatment, the acid-activated fly ash is dried.
9. The preparation method according to claim 1, characterized in that: Step (2) The content of aluminum oxide in the second fly ash is ≥40wt%.
10. The preparation method according to claim 1, characterized in that: The second fly ash is subjected to a second screening treatment before being mixed with the acid-activated fly ash.
11. The preparation method according to claim 10, characterized in that: The size of the sieve holes in the second screening process is 60-300 meshes.
12. The preparation method according to claim 11, characterized in that: The size of the sieve holes in the second screening process is 100-150 meshes.
13. The preparation method according to claim 1, characterized in that: The mixed powder in step (2) also includes 0.1 to 10 parts by weight of bauxite.
14. The preparation method according to claim 13, characterized in that: The content of aluminum oxide in the bauxite is greater than 60wt%.
15. The preparation method according to claim 13, characterized in that: The bauxite is subjected to a third screening treatment before being mixed with the acid-activated fly ash.
16. The preparation method according to claim 15, characterized in that: The size of the sieve holes in the third screening process is 100-300 meshes.
17. The preparation method according to claim 16, characterized in that: The size of the sieve holes in the third screening process is 100-200 meshes.
18. The preparation method according to claim 1, characterized in that: The mixed powder also includes 0.1 to 10 parts by mass of kaolin.
19. The preparation method according to claim 18, characterized in that: The kaolin is subjected to a fourth screening treatment before being mixed with the acid-activated fly ash.
20. The preparation method according to claim 19, characterized in that: The size of the sieve holes in the fourth screening process is 100-300 meshes.
21. The preparation method according to claim 20, characterized in that: The size of the sieve holes in the fourth screening process is 100-200 meshes.
22. The preparation method according to claim 1, characterized in that: The mass fraction of water in step (3) in the mixed powder is 10-25wt%.
23. The preparation method according to claim 1, characterized in that: The water and the mixed powder are mixed for 1 to 30 minutes.
24. The preparation method according to claim 1, characterized in that: The mixing of water and mixed powder includes step-by-step mixing or all-at-once mixing.
25. The preparation method according to claim 24, characterized in that: The mixing of the water and the mixed powder is step-by-step mixing.
26. The preparation method according to claim 24, characterized in that: The step-by-step mixing includes first adding water accounting for 5-15 wt% of the mixed powder and mixing with the whole mixed powder for 0.5-20 minutes, and then adding the remaining water and continuing to mix.
27. The preparation method according to claim 1, characterized in that: The equipment used in the granulation process includes any one of an inclined intensive mixer, a sugar coating pan or a disc granulator.
28. The preparation method according to claim 1, characterized in that: The equipment used in the granulation process is an inclined strong mixer.
29. The preparation method according to claim 27, characterized in that: The barrel speed of the inclined intensive mixer is 20-80 r / min.
30. The preparation method according to claim 27, characterized in that: The rotor speed of the inclined intensive mixer is 500-4000 r / min.
31. The preparation method according to claim 1, characterized in that: The granulation treatment time is 1 to 30 minutes.
32. The preparation method according to claim 1, characterized in that: The sintering process in step (3) includes heating the semi-finished product obtained by granulation from room temperature to a sintering temperature and then keeping the temperature.
33. The preparation method according to claim 32, characterized in that: The heating rate is 5-20°C / min.
34. The preparation method according to claim 32, characterized in that: The sintering temperature is 1200-1700°C.
35. The preparation method according to claim 32, characterized in that: The insulation time is 0.5 to 10 hours.
36. The preparation method according to claim 32, characterized in that: After the heat preservation, the furnace is naturally cooled.
37. The preparation method according to claim 1, characterized in that The preparation method comprises the following steps: (1) mixing the first fly ash with an acid solution having a concentration of 0.5 to 3 mol / L, performing an acid activation treatment, and obtaining acid-activated fly ash; The first fly ash is low-aluminum fly ash; the content of aluminum oxide in the first fly ash is ≤35%, the content of calcium oxide is >10wt%, and the content of silicon dioxide is >30wt%; the first fly ash is subjected to a first screening process before being mixed with the acid solution; the size of the sieve hole in the first screening process is 100-300 mesh; the acid solution includes H2SO4 solution and / or HCl solution; the ratio of the volume of the acid solution to the mass of the first fly ash is 5-15L / g; The temperature of the acid activation treatment is 50-130° C.; the time of the acid activation treatment is 0.5-12 hours; and after the acid activation treatment, the acid-activated fly ash is dried; (2) Mixing 10 to 40 parts by weight of the acid-activated fly ash and 50 to 100 parts by weight of the second fly ash to obtain a mixed powder; The second fly ash is high-aluminum fly ash; the content of aluminum oxide in the second fly ash is greater than 35wt%, and the content of silicon dioxide is greater than 30wt%. The second fly ash is subjected to a second screening process before being mixed with the acid-activated fly ash; the size of the sieve hole in the second screening process is 60-300 mesh; the mixed powder further includes 0.1-10 parts by weight of bauxite; the content of aluminum oxide in the bauxite is greater than 60wt%; the bauxite is subjected to a third screening process before being mixed with the acid-activated fly ash; the size of the sieve hole in the third screening process is 100-300 mesh; the mixed powder further includes 0.1-10 parts by weight of kaolin; the kaolin is subjected to a fourth screening process before being mixed with the acid-activated fly ash; the size of the sieve hole in the fourth screening process is 100-300 mesh; (3) After mixing water with the mixed powder for 1 to 30 minutes, granulation treatment, drying and sintering treatment are sequentially performed for 1 to 30 minutes to obtain the fly ash-based sintered ceramsite proppant; the mass fraction of water in the mixed powder is 10 to 25wt%; the mixing of water and the mixed powder includes step-by-step mixing or one-time mixing; the step-by-step mixing includes first adding water with a mass fraction of 5 to 15wt% of the mixed powder and mixing with the whole mixed powder for 0.5 to 20 minutes, and then adding the remaining water to continue mixing ; The equipment used in the granulation treatment includes any one of an inclined intensive mixer, a sugar coating pan or a disc granulator; the barrel speed of the inclined intensive mixer is 20~80r / min; the rotor speed of the inclined intensive mixer is 500~4000r / min; the sintering process includes heating the semi-finished product obtained by the granulation treatment from room temperature at a heating rate of 5~20℃ / min to a sintering temperature of 1200~1700℃, keeping it warm for 0.5~10h, and then cooling it naturally with the furnace.
38. A fly ash-based sintered ceramsite proppant, characterized in that: The fly ash-based sintered ceramsite proppant is prepared by the preparation method of the fly ash-based sintered ceramsite proppant according to any one of claims 1 to 37.
39. A use of a fly ash-based sintered ceramsite proppant, characterized in that: The fly ash-based sintered ceramsite proppant described in claim 38 is used in the process of oil or natural gas extraction.
Citation Information
Patent Citations
Method for preparing fracturing proppant by using pulverized fuel ash
CN102718523A
Low-density ceramic proppant prepared from fly ash and preparation method thereof
CN102899015A
Fly ash-containing petroleum fracturing propping agent and preparation method thereof
CN107365579A
Preparation method of ceramic granules
CN102060562A
Method for preparing oil fracturing proppant from high-aluminum fly ash
CN104371703A